The Kremlin playbook : understanding Russian influence in Central and Eastern Europe - Conley, Heather A.; Mina, James; Stefanov, Ruslan; Vladimirov, Martin (CSIS report., 2016)
Russia has cultivated an opaque web of economic and political patronage across the Central and Eastern European region that the Kremlin uses to influence and direct decisionmaking.